a Pengembangan Perangkat Pembelajaran Berbasis SETS Melalui Direct Instruction Berbasis Pemecahan Masalah Terkait Kompetensi Agribisnis tanaman pangan dan holtikultura : ardiansyah - Ardiansyah Bima (STKIP Al-Amin Dompu, 2022)
Plant Breeding Learning at SANGGAR 1 Vocational School related to competency Agribusiness Food Crops (AFC) expertise has not implemented the vision of Science, Environment, Technology and Society (SETS), nor has it implemented direct learning. This study aims to test the validity, effect of learning outcomes and the effectiveness of learning devices. The type of research used is Research and Development (R&D). Large-scale trials were conducted in the experimental and control class with 30 students each. Design large-scale trial research using Pretest-posttest Control Group Design. The product developed was in the form of syllabus, lesson plans, teaching materials, LKPD and evaluation questions. From the results of research and development obtained a very valid and very effective learning device to be used because according to the results of validation from experts and student learning outcomes in cognitive, affective and psychomotor aspects achieve completeness KKM 70. Classically 97% (29 students completed), the value of N-gain is 0.5 in the medium category, and the results of the t-test are greater than the value of the table (5.64> 2.00) at the significance level α = 0.05 means the hypothesis is accepted. Positive responses from students and teachers state that the learning tools developed are very practical and very effective to use. From the information and data analysis that the SETS Biology vision learning device through direct insturuction based on problem solving related to environmental pollution competencies can be concluded to be very effective and can improve student learning outcomes on Cognitive, Affective and Psychomotor aspects.